A novel fully covered metal stent for unresectable malignant distal biliary obstruction: results of a multicenter prospective study - Arata Sakai; Atsuhiro Masuda; Takaaki Eguchi; Keisuke Furumatsu; Takao Iemoto; Shiei Yoshida; Yoshihiro Okabe; Kodai Yamanaka; Ikuya Miki; Saori Kakuyama; Yosuke Yagi; Daisuke Shirasaka; et al. (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims Endoscopic self-expandable metal stent (SEMS) placement is currently the standard technique for treating unresectable malignant distal biliary obstructions (MDBO). Therefore, covered SEMS with longer stent patency and fewer migrations are required. This study aimed to assess the clinical performance of a novel, fully covered SEMS for unresectable MDBO. Methods This was a multicenter single-arm prospective study. The primary outcome was a non-obstruction rate at 6 months. The secondary outcomes were overall survival (OS), recurrent biliary obstruction (RBO), time to RBO (TRBO), technical and clinical success, and adverse events. Results A total of 73 patients were enrolled in this study. The non-obstruction rate at 6 months was 61%. The median OS and TRBO were 233 and 216 days, respectively. The technical and clinical success rates were 100% and 97%, respectively. Furthermore, the rate of occurrence of RBO and adverse events was 49% and 21%, respectively. The length of bile duct stenosis (<2.2 cm) was the only significant risk factor for stent migration. Conclusions The non-obstruction rate of a novel fully covered SEMS for MDBO is comparable to that reported earlier but shorter than expected. Short bile duct stenosis is a significant risk factor for stent migration.